Policy Evaluation of Assistance Program Operational School (Case Studies on Junior High School Country 17 Medan, Bandar Selamat, Kec. Medan Tembung, City Medan) - Surbakti, Fina Aprilia; Simanjuntak, Jessica Evi; Pascha S, Teddy; Ivanna, Julia (Berpusi Publishing, 2023)
Education is a key element in the development process of a country and determines the country's economic growth. Education is also an investment in the development of human resources, and the development of skills and competencies is seen as an element that supports human efforts to deal with the uncertainties of life. One of the initiatives within the Education Office program that received a significant budget allocation was the 'School Operational Assistance (BOS)'. The School operational assistance Program (BOSS) reduces the costs that must be incurred by the community to carry out the 12 year compulsory education. Monitoring of this policy is necessary to ensure that the policy is properly implemented. Medan City is a city of education and also has a school management support program. Evaluation of the School Management Assistance Fund policy really needs to be done because there is nothing wrong with using Agra. The type of research used is descriptive research using a qualitative approach. The data collection was carried out using observation, interviews and documentation techniques which were then analyzed using descriptive analysis techniques. The results showed that the process of implementing the BOS fund policy at the school level and at the city level at SMP Negeri 17 Medan has been well managed in accordance with the procedures set out in the BOS Funding Guidelines. in this case, the role of the community is needed as input and monitoring of the BOS program funds.